KODIFIKASI SASTRA ARAB PERIODE KLASIK (JAHILY) - Mustamar, Marzuki (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2006)
â€œAyyam al-Arabâ€ and â€œal-Ansabâ€ which recorded, both in the form of genre prosa and genre poetry is an authentic evidence that show jahiliyah society have produced literary works. Those two sources were dig up by hammad al-Rawiyyah when he codified jahiliâ€™s literary works.